From foreign aid to domestic debt: essays on government financing in developing economies - Abbas, S (2014)
The first essay [“Twin Deficits and Free Lunches: Macroeconomic Outcomes In Anticipation of Foreign Aid”] concerns itself with situations in which private agents anticipate a future windfall (free lunch) that will help service the debt resulting from a present fiscal expansion (implemented via a temporary tax cut). Such expectations of a windfall can arise in the context of natural resource discoveries or, more interestingly, due to perceptions by agents in “too important to fail” countries that will be bailed out through higher foreign aid or debt relief. We employ an overlapping generations model featuring credit constraints to study the real effects of such free lunch expectations in a small open economy, drawing contrasts with the standard tax and money finance closure rules. The model is solved analytically and shows that anticipated aid is equivalent to current aid when agents have perfect foresight, so that a temporary tax cut is seen as permanent. Accordingly, agents raise their consumption and indebtedness (at the expense of future generations) by an amount that is an increasing function of their “impatience” (subjective rates of time preference plus probability of death). A worsening of the current account obtains (twin deficits) across a range of plausible closure rules, including those featuring money finance. The introduction of credit constrained households (we study the variant where myopic agents spend their current disposable incomes) does not alter the basic result in the case of full aid finance, but does matter for mixed tax-aid regimes, in more complex settings where agent expectations and donor promises on aid diverge, and when governments face borrowing constraints so that the timing of aid delivery matters. The second essay [“The Role of Domestic Debt in Economic Growth: An Empirical Investigation For Developing Economies”] focuses on the remaining source of government financing, i.e. domestic debt, and the role it can play in mobilizing private savings, facilitating credit intermediation in higher risk settings (i.e. serving a “collateral” function on bank balance sheets), developing financial markets and supporting economic growth in general. To investigate this question empirically, we set up a new domestic debt database covering about 100 developing economies, going back three decades to 1975; explore Granger causality links between domestic debt and key macroeconomic and institutional variables; and estimate the growth impact of domestic debt using panel regressions, allowing for non-linear effects. Domestic debt, as a share of GDP is found to exert a significant positive impact on economic growth, with potential channels including domestic savings mobilization, provision of risk-insurance on banks’ balance sheets; and greater institutional accountability of the state to its citizens. Although this result countervails more established arguments against domestic debt (i.e. that it leads to crowding out and banks to become lazy), there is some evidence that above a ratio of 35 percent of bank deposits, domestic debt does begin to undermine economic growth. The growth payoff also depends on debt quality, with higher payoffs observed for positive interest-rate bearing marketable debt issued to nonbank sectors. The third and final essay [“Why Do Banks in Developing Economies Hold Domestic Government Securities?”] explores demand-side determinants of domestic debt, by focusing on commercial bank holdings of government paper, discriminating carefully between voluntary factors (such as mean-variance portfolio optimization) and statutory ones (cash reserve and capital adequacy requirements). The analysis is made possible by the construction of a dataset on government and private returns (real and nominal) for almost 600 banks from 70 emerging and low-income economies, spanning the (pre-Basel II) period 1995-2005. A battery of structural cross-section regressions indicates that banks’ portfolio decisions are at least as significantly influenced by mean-variance considerations as regulatory factors: the actual portfolio share of government securities (λ) responds intuitively, and sizably, to variations in the moments of the distributions for government and private returns as well as in the minimum-variance portfolio share (λ*). Higher cash reserve requirements tilt portfolios away from government securities toward riskier private lending, while higher capital adequacy requirements work the other way. The association between actual portfolios and the identified determinants is noticeably weaker at lower ends of the λ distribution, suggesting the domination of non-CAPM factors in those contexts.